Electro-discharge machining of alumina: investigation of material removal rate and surface roughness - Ali, Mohammad Yeakub; Moudood, M. A.; Maleque, Md. Abdul; Hazza Faizi Al Hazza, Muataz; Adesta, Erry Yulian Triblas (Faculty of Mechanical Engineering, Universiti Malaysia Pahang, 2017)
Alumina is a non-conductive ceramic material which can meet the high demand of industrial applications due to its excellent physical and chemical properties. However, machining of alumina is not possible by using the conventional machining methods due to its inherent brittleness. Recently, electro-discharge machining has been used for structuring alumina with assisting electrode to initiate the spark between the conductive tool electrode and the non-conductive work piece material. However, the effects of process parameters on material removal rate and surface roughness have not been investigated to formulate mathematical models. This study dealt with developing models for material removal rate and surface roughness correlating three process parameters which are peak current, pulse-on time and gap voltage using response surface methodology. The models were verified with 7% error between the results of empirical models and the experimental values.